Advertising and integrated brand promotion - O'Guinn, Thomas C.; Allen, Chris T.; Semenik, Richard J. (South-Western, Cengage Learning, 2012)
The authors draw from their vast business and teaching experience to integrate a solid understanding of advertising strategy and theory with hands-on, real applications. A leader for its emphasis on integrated brand promotion, this edition combines a compelling presentation of the fundamentals of advertising with invigorating coverage of the latest practices and industry developments, such as social media, design thinking, and the impact of globalization. Advertising strategy comes to life with more than 500 of today's most contemporary ads and exhibits. The book's content follows the same process as an advertising agency to equip readers with the tools, knowledge, and practice for effective results